Numerical Solution of Binary Liquid-Phase Adsorption onto Porocel Clay Using Linear, Freundlich and Langmuir Isotherms - Olaosebikan A. Olafadehan; Alfred A. Susu (Adsorption Science & Technology)
A generalized mathematical model is presented to describe the process of multi-component adsorption onto porous media in fixed beds. The model was applied to the binary adsorption, without reaction, of aromatics and sulphur compounds onto a fixed bed of Porocel clay for kerosene deodorization using linear, Freundlich and Langmuir isotherms independently. A computational scheme for the solution of the model equations is presented. The scheme is based on orthogonal collocation for spatial discretization of the resulting set of coupled hyperbolic and parabolic partial differential equations for the macro-and micro-system, respectively. Michelsen's modified third-order semi-implicit Runge-Kutta method combined with step-size adjustment strategy was used to integrate the resulting 4N ordinary differential equations. Excellent agreement between the simulated results and pilot plant data was obtained for the breakthrough profiles for the non-linear adsorption isotherms of Freundlich and Langmuir. No agreement was obtained for the linear isotherm. Also, using the Freundlich and Langmuir isotherms, the exit concentration of the less preferentially adsorbed component (aromatics) exceeded its inlet concentration to the adsorption column for a certain period. This is indicative of the behaviour of competitive multi-component adsorption: relative to aromatics, sulphur compounds are selectively adsorbed onto Porocel clay. The relationship between solid- and liquid-phase concentration profiles for the Freundlich isotherm revealed the formation of multiple adsorption layers upon the primary mono-molecular layer. Again, for the Freundlich isotherm, the structure of the profiles exhibited a highly pronounced maximum for sulphur. An experimental breakthrough time of 8 h was also predicted for both aromatics and sulphur compounds using the non-linear Freundlich and Langmuir isotherms.